Determination of Factors that Affect Health-Related Quality of Life in Health Sciences Students - Gezer, Ceren; Bakirezen, Ugur; Yalvac, Mesut (Galenos Publ House, 2024)
BACKGROUND/AIMS: The aim of this study was to evaluate health sciences students' health-related quality of life and the factors which affect it. MATERIALS AND METHODS: This study was conducted with 293 faculty of health sciences students who were selected using stratified sampling by department. A questionnaire about their demographic characteristics and the Short Form-36 (SF-36) were administered in face-to-face interviews, and some anthropometric measurements were made. RESULTS: The males' mean scores on the social functioning, pain and general health perception subscales of SF-36 were higher than those of the females (p<0.05). The non-smokers had higher mean scores on the physical role limitation, emotional role limitation, vitality, mental health and pain subscales of SF-36 than those who smoked (p<0.05). The sports science students had the highest scores on vitality, mental health, pain and general health perception (p<0.05). The students with low risk of cardiovascular disease according to their waist/height ratios had higher vitality scores (p<0.05). CONCLUSION: To conclude, gender, smoking, department and anthropometric measurements affected the quality of life of the health science students. In order to determine which factors affect quality of life, it may be useful to conduct more studies with larger samples.
Keywords: Health; lifestyle; quality of life; young adult; student